2016
DOI: 10.7150/jca.16925
|View full text |Cite
|
Sign up to set email alerts
|

Massive parallel sequencing and digital gene expression analysis reveals potential mechanisms to overcome therapy resistance in pulmonary neuroendocrine tumors

Abstract: Background: Lung cancer is the leading cause of cancer-related deaths worldwide. 25% show neuroendocrine differentiation (typical/atypical carcinoids, large-/small-cell neuroendocrine carcinomas). Carcinoids present with long survival rates, but metastatic carcinoids correlate with decreased survival and are commonly insensitive to standard chemotherapy or radiation. Therefore, novel therapeutic strategies are urgently needed.Material and methods: 70 representative tumor specimens were used for next-generation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…The mutations of KIT, ERBB4 and MET were also reported in these studies, which supported the findings of the present study (27)(28)(29). Notably, one study that used NGS to investigate carcinoids did not provide the original sequencing data and, consequently, the sequencing results were not summarized in Table III; however, it was reported in the study that FGFR1 was highly expressed in carcinoids (39). In addition, Rossi et al (40) also reported that ERBB4 alteration was detected in carcinoids.…”
Section: Discussionsupporting
confidence: 90%
“…The mutations of KIT, ERBB4 and MET were also reported in these studies, which supported the findings of the present study (27)(28)(29). Notably, one study that used NGS to investigate carcinoids did not provide the original sequencing data and, consequently, the sequencing results were not summarized in Table III; however, it was reported in the study that FGFR1 was highly expressed in carcinoids (39). In addition, Rossi et al (40) also reported that ERBB4 alteration was detected in carcinoids.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have investigated carcinoid tumours using non‐ in‐situ techniques. A next‐generation sequencing (NGS) analysis of 14 ‘druggable’ genes in 70 neuroendocrine tumours and mRNA‐expression profiles of 60 matching samples were determined for 13 selected drug targets using NanoString nCounter technology (NanoString Technologies, Inc., Seattle, WA, USA) . In this study, EGFR expression was observed in 87.5% of TC, 100% of AC, 65.3% of LCNEC and 60% of SCLC.…”
Section: Carcinoid Tumoursmentioning
confidence: 95%
“…In addition, MDM2 was expressed strongly in most samples, whereas the expression of its physiological inhibitor, CDKN2A , was almost absent in all TC. TP53 showed a high frequency of variants in high‐grade tumours, but mutations were rare in carcinoids …”
Section: Carcinoid Tumoursmentioning
confidence: 99%
“…Overall, more than half of poorly differentiated GI NECs have somatic TP53 mutations, while 0-11% of moderately and well-differentiated GI NETs harbor the mutation [2,5,10,11]. Similarly, for pulmonary NETs, more than 60% of small cell lung cancer and large cell neuroendocrine carcinoma have TP53 mutations, and 0-11% of well-differentiated grade 1 and 2 pulmonary NETs have been shown to have TP53 mutations [12,13].…”
Section: Discussionmentioning
confidence: 99%